Educational Policy and Curriculum Innovation: A Study on Impactful Learning in Primary Schools - Arsalim, Arsalim; Parisu, Chairan Zibar L.; Saprudin, Saprudin (Newinera Publisher, 2025)
This study focuses on the implications of Kurikulum Merdeka to pedagogical delivery and student motivation in primary schools and the subjective institutional and infrastructural environment through which it is carried out. As it uses a convergent mixed-methods design, the study combines environmental scans administered to 100 teachers and 20 principals with qualitative classroom observations and interviews of urban and rural schools in Kendari. The results show that even though several teachers support the declared goals of practitioner-led, situation-based learning of the curriculum, the level of its implementation is strongly subject to the long-term professional growth of the teachers as well as enough availability of materials. The urban schools associate with more effective learning patterns, reinforced with better infrastructure and collaborative pedagogy ethic, and the rural teachers often establish a tradeoff against pedagogical change. Qualitative reviews show that once learners are involved in authentic and community-oriented activities, their agency, ethical sensibility, and learning self-regulation increase. Nevertheless, the results still hang uncertainly on the conditions, evenly and otherwise distributed, that are their conditions. This research supports the argument that the success of the Independent Curriculum ultimately depends not only on particular design features but also on the systematic appreciation of the teacher, fair learning conditions offered and the development of the school culture that does not treat innovation as an invariable prescription.